The appendix ¿No? in colloquial Spanish conversation - Montañez Mesas, Marta Pilar (Boletín de Filología, 2008)
This paper attempts to describe the pragmatic functions of discourse markers applying a purely distributional criterion, that is, their position in the talk units. Specifically, we focus on final position because most papers deal with initial position. To apply this criterion, we rely on the units of conversation proposed by Grupo Val.Es.Co. Thus, our object of study are discourse particles or discourse markers like ¿eh?, ¿no?, ¿sabes?, ¿entiendes?, ¿comprendes?, to the extent that they take final position. In this study, we concentrate on the appendix ¿no? because of three reasons: first, its high frequency in our corpus; second, its polyfunctionality and, third, because it enables us to demonstrate the applicability and profitability of the distributional criterion in the study of discourse markers in conversation.